MTOR signaling, Tregs and immune modulation. (December 2014) - Chapman, Nicole M; Chi, Hongbo
Foxp3 + Tregs are central regulators of immune tolerance. As dysregulated Treg responses contribute to disease pathogenesis, novel approaches to target the immunomodulatory functions of Tregs are currently under investigation. mTORC1 and mTORC2 are therapeutic targets of interest. Recent studies revealed that mTOR signaling impacts conventional T-cell homeostasis, activation and differentiation. Moreover, mTOR controls the differentiation and functions of Tregs, suggesting that its activity could be targeted to modulate Treg responses. Here, we summarize how Tregs suppress immune responses, their roles in disease development and methods used to alter their functions therapeutically. We also discuss the diverse effects exerted by mTOR inhibition on the development, homeostasis, and functions of conventional T cells and Tregs. We conclude with a discussion of how modulation of mTOR activity in Tregs may be therapeutically beneficial or detrimental in different disease settings.